2017
DOI: 10.1080/13607863.2017.1348469
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drug prescription for nursing home residents with dementia: prevalence and associations with non-resident-related factors

Abstract: Prescription rates for antipsychotics are similar compared to other countries, and relatively low for antidepressants, anxiolytics, and hypnotics. Our findings indicate that improvement of prescribing could provisionally best be targeted at resident-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
(52 reference statements)
2
17
1
Order By: Relevance
“…Second, we were unable to operationalize the correction for the occurrence of neuropsychiatric symptoms throughout the study in the analyses. Knowing that neuropsychiatric symptoms are the most important factor for prescription of psychotropic drugs, we would have preferred to include these in our model (Smeets et al, 2017). However, this would have raised the issue of how to operationalize this correction.…”
Section: Trial Conductmentioning
confidence: 99%
“…Second, we were unable to operationalize the correction for the occurrence of neuropsychiatric symptoms throughout the study in the analyses. Knowing that neuropsychiatric symptoms are the most important factor for prescription of psychotropic drugs, we would have preferred to include these in our model (Smeets et al, 2017). However, this would have raised the issue of how to operationalize this correction.…”
Section: Trial Conductmentioning
confidence: 99%
“…Despite the warnings and the plethora of studies conducted across various settings and countries reporting adverse effects of these drugs, the use of APMs in the nursing home setting is reported to be high [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The prevalence of APM use in nursing homes varies significantly between countries, with reports ranging from 12% to >50% prevalence [16,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…These authors found access to consultants and the nursing home setting to be relevant. Interestingly, a more recent quantitative analysis by this group, questions the extent to which nonresident‐related factors are associated with psychotropic drug prescription (Smeets et al., ). There is already strong evidence that the unit size, spatial layout, homelike character, sensory stimulation, and environmental characteristics of social spaces effect the behaviours and well‐being of people with dementia living in care facilities (Chaudhury, Cooke, Cowie, & Razaghi, ).…”
Section: Discussionmentioning
confidence: 99%